Mathematical Formulae - Norazaliza, Mohd Jamil; Nor Alisa, Mohd Damanhuri; Yuhani, Yusof; Nor Aida Zuraimi, Md Noar; Norhafizah, Md Sarif (Penerbit UMP, 2017)
Mathematical Formulae intends to provide students, scientists, engineers, and researchers with a readily available reference to the mathematical formulae needed during their studies or work situation. It is a handy book that one must have on the bookshelf. The text is divided, for ease of reference, into ten main chapters embracing algebra, trigonometry, limit, differentiation and integration, vector calculus, coordinate geometry, differential equations, numerical methods, discrete mathematics, and ﬁnancial mathematics. Essential theory, formulae, deﬁnitions and laws are clearly stated in this book